2023
DOI: 10.1111/jne.13269
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic metastases in patients with neuroendocrine neoplasms: A multi‐centre cohort study

Abstract: Pancreatic metastases (PMs) from neuroendocrine neoplasms (NENs) are rare but the increased sensitivity of new diagnostic tools such as 68 Ga-DOTATATE PET/CT has resulted in their increased recognition at initial diagnosis or follow-up.A retrospective analysis of the data of patients from six tertiary referral centres was performed in order to identify the characteristics and the prognostic significance of PMs in patients with NENs. We used a control group of 69 age-, sexand primary tumourmatched NEN patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…11 To date, comprehensive descriptive and survival analyses in patients with rare metastases are sparse. 3,7,8,13,20,24 Of note, earlier studies have reported significantly shorter OS for patients with bone metastases, as compared to patients with other types of distant metastases. 3,10 The prevalence of Virchow's lymph node metastasis among patients with abdominal and thoracic malignancies has previously been estimated to be up to 2.8%.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…11 To date, comprehensive descriptive and survival analyses in patients with rare metastases are sparse. 3,7,8,13,20,24 Of note, earlier studies have reported significantly shorter OS for patients with bone metastases, as compared to patients with other types of distant metastases. 3,10 The prevalence of Virchow's lymph node metastasis among patients with abdominal and thoracic malignancies has previously been estimated to be up to 2.8%.…”
Section: Discussionmentioning
confidence: 95%
“…Orbital lesions show low prevalence and are more commonly associated with Si-NET than Pan-NET, 5,13,14 which was confirmed by Interestingly, in a recent study in patients with Si-NET, pancreatic metastases had no impact on OS, when compared to matched controls. 8 Pan-NETs and Si-NETs both represent heterogeneous diseases, displaying a variable behaviour from a spectrum of relatively indolent to highly aggressive. These tumours, originating from different locations, indeed display many differences also from a molecular point of view, as they are related to different genetic or hormone-derived syndromes, display different driver alterations, and often display a wide spectrum of outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations